1999
DOI: 10.1046/j.1365-2559.1999.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of histomorphometric nuclear parameters in the diagnosis of well differentiated follicular carcinomas and follicular adenomas of the thyroid gland

Abstract: Histomorphometrically gauged nuclear parameters of the tumour cells may reinforce pathologists' decision-making by adding objective and unbiased criteria to their subjective assessment of follicular neoplasms in cases in which vascular or capsular invasion are not detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 7 publications
(10 reference statements)
1
15
0
6
Order By: Relevance
“…Therefore, computerized morphometry is more reproducible and increases its potential diagnostic value. 5,9,11,13 In the present study, the cytopathologic morphometric data indicated a correlation between MNA and patient survival; Kaplan-Meier analysis demonstrated that survival times were significantly shorter as nuclear area increased. These results corroborate previous data that demonstrate a relationship between morphometric analysis and histopathologic grading 22,34 and confirm the usefulness of cytomorphometry alone as a predictor of survival.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, computerized morphometry is more reproducible and increases its potential diagnostic value. 5,9,11,13 In the present study, the cytopathologic morphometric data indicated a correlation between MNA and patient survival; Kaplan-Meier analysis demonstrated that survival times were significantly shorter as nuclear area increased. These results corroborate previous data that demonstrate a relationship between morphometric analysis and histopathologic grading 22,34 and confirm the usefulness of cytomorphometry alone as a predictor of survival.…”
Section: Discussionsupporting
confidence: 56%
“…The immunohistochemically stained sections were analyzed by light microscopy and the images were digitalized using a video camera (Sony, Japan) attached to a personal computer (Penthium MMX 450 MHz), equipped with frame grabber as has been described by one of us [27]. The images were displayed in color (RGB) on a 17-inch high-resolution computer monitor (1,200 !…”
Section: Image Analysismentioning
confidence: 99%
“…The recommended usual management for atypia is to repeat the FNA (9). So far, no preoperative clinical assays can reliably determine which of these patients should undergo surgery (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%